Values Transmission through English Textbooks for Secondary School Students and its influence on their perception of the Islamic identity - Souad, Merah; Ramdane, Tahraoui; Husin, Nor Hayati (2015)
his paper is based on a research grant that was conducted by the team, and aimed at studying the values transmission through the western English textbooks and their effect on secondary Muslim students’ perception about the Islamic personality and teachings at the International Islamic School Malaysia (IISM)